The role of the Glorious Qur’an in achieving societal peace in Salah al-Din Governorate - Esraa Tohme Ali (Islamic Sciences Journal, 2026)
ABSTRACT Societal peace is a basic necessity for the stability and growth of societies, and Islam has paid great attention to this issue, as the Glorious Qur'an came with its comprehensive directives that call for peaceful coexistence, the rejection of strife and conflicts, and the consolidation of the values of justice and tolerance. The Qur'anic teachings contribute to strengthening societal peace and help achieve social stability. Salah al-Din Governorate is an example of a diverse society that has witnessed various challenges that require the promotion of societal peace through Islamic values derived from the Glorious Quran.